Ectopic Transcript Analysis Indicates that Allelic Exclusion is an Important Cause of Type I Protein C Deficiency in Patients with Nonsense and Frameshift Mutations in the PROC Gene - Soria, José Manuel; Berg, Lutz-Peter; Fontcuberta, Jordi; Kakkar, Vijay V; Estivill, Xavier; Cooper, David N; Sala, Núria (Thrombosis and Haemostasis, 1996)
Nonsense mutations, deletions and splice site mutations are a common cause of type I protein C deficiency. Either directly or indirectly by altering the reading frame, these' lesions generate or may generate premature stop codons and could therefore be expected to result in premature termination of translation. In this study, the possibility that such mutations could instead exert their pathological effects at an earlier stage in the expression pathway, through “allelic exclusion” at the RNA level, was investigated. Protein C (PROC) mRNA was analysed in seven Spanish type I protein C deficient patients heterozygous for two nonsense mutations, a 7bp deletion, a 2bp insertion and three splice site mutations. Ectopic RNA transcripts from patient and control lymphocytes were analysed by RT-PCR and direct sequencing of amplified PROC cDNA fragments. The nonsense mutations and the deletion were absent from the cDNAs indicating that only mRNA derived from the normal allele had been expressed. Similarly for the splice site mutations, only normal PROC cDNAs were obtained. In one case, exclusion of the mutated allele could be confirmed by polymorphism analysis. In contrast to these six mutations, the 2 bp insertion was not associated with loss of mRNA from the mutated allele. In this case, cDNA analysis revealed the absence of 19 bases from the PROC mRNA consistent with the generation and utilization of a cryptic splice site 3’ to the site of mutation, which would result in a frameshift and a premature stop codon. It is concluded that allelic exclusion is a common causative mechanism in those cases of type I protein C deficiency which result from mutations that introduce premature stop codons